Democracy's education : public work, citizenship, & the future of colleges and universities - Boyte, Harry C., 1945- (Vanderbilt University Press, 2015)
"Democracy's Education shows possibilities for educators to be agents, not victims, of changes sweeping higher reeducation. Framed by Harry Boyte's challenge for educators to claim their hidden powers, it brings world-famous scholars, government officials, and presidents together with faculty, students, staff, and community organizers to show constructive responses happening now"--